The impact of certification on the natural and financial capitals of Ghanaian cocoa farmers - Fenger, N.A.; Bosselmann, A.S.; Asare, R.; Neergaard, Andreas de (Informa UK Limited, 2017)
While an increasing number of large food companies commit themselves to source only certified cocoa, research on the impacts of certification on cocoa farmers is falling behind. We investigate how Rainforest Alliance (RA) certification of smallscale cocoa farmers in Ghana has affected both the financial and the natural capitals of the farmers. Across two villages, certified farmers were compared to conventional farmers, using both qualitative and quantitative data collected through farmer and key informant interviews and participatory rural appraisals. A combination of the Sustainable Livelihood Framework and the input–output–outcome–impact framework was used for the analysis. Results indicate that the RA certification scheme has a positive influence on the certified farmers in terms of cocoa production, yield, income, and farmers’ perception of changes in their natural and financial capitals. The positive influence is a result of inputs from the RA certification, including financial support, information and knowledge, technical assistance, and increased access to farm inputs and credit. However, these positive impacts are conditioned by the presence of active farmer organizations and access to agricultural inputs and credit through associations and government institutions, and may be undermined by certified farmers who sell their produce outside the premium value chain.